2021
DOI: 10.1111/1750-3841.15657
|View full text |Cite
|
Sign up to set email alerts
|

Study on the structure and digestibility of high amylose Tartary buckwheat (Fagopyrum tataricum Gaertn.) starch‐flavonoid prepared by different methods

Abstract: Tartary buckwheat (Fagopyrum tataricum Gaertn.) is the only food rich in flavonoid bioactive substances in grains. Studies have shown that flavonoids interaction with amylose has an important impact on the physical and chemical properties and structure of starch. In this study, Tartary buckwheat was used as a raw material. It was then threshed with pullulanase, and a high amylose Tartary buckwheat starch flavonoid complex (HBS/BF) was prepared by physical mixing (PM), water bath treatment (WT), acid-base preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The overall pooled LFUS treatment causes a slight decrease (0.97 J/g) in ΔH, a tendency also observed by Amini et al [140] , Boufi et al [143] , Li et al [145] , Huang et al [148] , Zhou et al [150] and Yu et al [156] . The decrease in ΔH was related to the loss of amylopectin double helices, essential structures for granule integrity preservation [157] .…”
Section: Effect Of Low-frequency Ultrasound On Cereals and Pseudocere...supporting
confidence: 76%
See 1 more Smart Citation
“…The overall pooled LFUS treatment causes a slight decrease (0.97 J/g) in ΔH, a tendency also observed by Amini et al [140] , Boufi et al [143] , Li et al [145] , Huang et al [148] , Zhou et al [150] and Yu et al [156] . The decrease in ΔH was related to the loss of amylopectin double helices, essential structures for granule integrity preservation [157] .…”
Section: Effect Of Low-frequency Ultrasound On Cereals and Pseudocere...supporting
confidence: 76%
“…Furthermore, the number average molecular weight ( M n ) and polydispersity ( M w ∕M n ) diminished with sonication time and their decreasing rate was related to temperature and power [149] . Due to these events, Zhou et al [150] indicated LFUS as the best alternative to produce flavonoids-enriched starch complex from Tartary buckwheat. In addition, they saw an increase in resistant starch (+20%) and a slower starch digestion.…”
Section: Effect Of Low-frequency Ultrasound On Cereals and Pseudocere...mentioning
confidence: 99%
“…KS‐6 can be used as an ideal functional starch. Meanwhile, some studies have shown that flavonoids have a significant effect on the digestive (Lin et al., 1996) and processing properties of starch (Zhou et al., 2021), suggesting that KS‐6 may have different properties and is worthy of further study.…”
Section: Resultsmentioning
confidence: 99%
“…Seeds are the edible organs of plants, and starch accounts for the highest proportion of the dry weight of seeds in Tartary buckwheat [ 12 ]. A food’s quality and taste are greatly influenced by its starch content, especially amylose and the ratio of amylose to amylopectin [ 6 , 7 , 8 ]. Previous studies have reported that the amylose content of Tartary buckwheat seeds ranged from 10% to 28% [ 5 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Starch, comprised of amylose and amylopectin, is the major component of Tartary buckwheat seeds, accounting for the highest proportion of their dry weight [ 5 ]. Starch content, especially amylose content and the ratio of amylose to amylopectin content (amylose/amylopectin), affects food quality and taste to a great degree [ 6 , 7 , 8 ]. The amylose content of Tartary buckwheat seeds ranges from 10–28%, which depends on the germplasm difference and also differences in measurement method [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%